Print with collage and stitch : techniques for mixed-media printmaking - Holmes, Val. (Loveland : Interweave Press, 2012)
"The enthralling popularity of collography is taking textile artists to new heights. Learn this popular new technique from the best when you explore collography with embroidery teacher, Val Holmes. In her new book, Print with Collage and Stitch, Holmes shares everything you need to know about the exciting effects of combining almost endless permutations of collage, stitch, and print and how to incorporate these effects into your own stitched-textile work. Included is invaluable and beautifully illustrated information on embroidered collography plate-making, choosing the right printing surface, combining paper and fabric, embroidering onto prints, and how to work in a series. In addition to innovative collography techniques, you'll discover an in-depth look into monoprinting and incorporating common textile art techniques into serial monoprints. In Print with Collage and Stitch, you'll explore a simple and most fundamental mixed-media technique, popular for producing highly-sophisticated and complex-looking surface effects"--
"Learn the secrets of the textile art technique collography"--
Machine generated contents note: Chapter 1 Making the plate --Materials suitable for making the plate and for adding to the plate --How to make a plate --How to protect the plate for printing --Chapter 2 Introducing brodagraphy --How to make a collography plate using embroidery --Chapter 3 Printing from the plate without a press --Chapter 4 Printing with a press --Different types of press that can be used --Developing a print using different color and application techniques. --Chapter 5 Surfaces for print --A look at different papers and fabrics suitable for printing --Chapter 6 Collagraphy for paper relief --Chapter 7 Embroidering the print --Techniques for embroidery on paper to enhance the paper print --Embroidery onto a textile print --Printing onto textile surfaces that can be heated and distorted afterward --Chapter 8 The monotype --Using some of the above techniques for serial monotypes --Conclusion Exploiting prints in your work --Appendix: The press --Different solutions for bought presses and suggestions for borrowing --Clear plans and instructions for the construction of two different types of press --Suppliers.
Includes bibliographical references and index.
Keywords: Collagraph printing -- Technique